2006
DOI: 10.4141/a06-014
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium bicarbonate, offered free choice or blended into the ration, to reduce the risk of ruminal acidosis in cattle

Abstract: . and von Keyserlingk, M. A. G. 2006. Use of sodium bicarbonate, offered free choice or blended into the ration, to reduce the risk of ruminal acidosis in cattle. Can. J. Anim. Sci. 86: 429-437. A study was conducted to determine whether feeding sodium bicarbonate (SB) reduces the risk of subacute ruminal acidosis in cattle fed high concentrate feedlot finishing diets. The experiment was conducted as a replicated 3 × 3 Latin square design with two squares and 2-wk periods. Three mature, non-lactating Holstein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
(65 reference statements)
0
13
0
1
Order By: Relevance
“…Similarly, SARA-challenged cows did not show a preference for water with sodium bicarbonate added (Cottee et al, 2004). Nonchallenged cows showed no preference for sodium bicarbonate mixed in the ration or offered free choice, although the former reduced the number of long bouts of acidosis per day (Paton et al, 2006).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, SARA-challenged cows did not show a preference for water with sodium bicarbonate added (Cottee et al, 2004). Nonchallenged cows showed no preference for sodium bicarbonate mixed in the ration or offered free choice, although the former reduced the number of long bouts of acidosis per day (Paton et al, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Several methods have been used in attempts to control acidosis. Sodium bicarbonate is commonly added to rations, but the effect on pH is variable depending on experimental conditions (e.g., Hu and Murphy 2005;Paton et al, 2006). Monensin is added to almost all feedlot rations to improve feed efficiency with benefits of reducing acidosis likely due to decreased intake; however, effects on pH are only moderate or not observed under experimental conditions (Mutsvangwa et al, 2002;Benchaar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that ruminants allowed to choose among ingredients were able to select diets according to their needs (Atwood et al, 2001;Moya et al, 2011). However, research that measured ruminal pH in relation to selection of dietary ingredients has not substantiated this claim (Keunen et al, 2003;Paton et al, 2006). However, research that measured ruminal pH in relation to selection of dietary ingredients has not substantiated this claim (Keunen et al, 2003;Paton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several dietary strategies proposed for use in preventing SARA, such as sodium bicarbonate and monensin, have been studied [12,13]. However, neither of these methods has consistently maintained higher rumen pH values.…”
Section: Introductionmentioning
confidence: 99%